Flicker problem assessment of different wind turbine models in a distribution system - Krongsiri Mongkholkaset; Singh, Jai Govind; Weerakorn Ongsakul; Dhakal, Shobhakar; PEA; Asian Institute of Technology Education Cooperation Project; Asian Institute of Technology Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2014)
In the distribution systems, the wind turbine installation may cause problems on power quality during continuous operations. The main power quality problems are voltage fluctuation, flicker and harmonics. Power fluctuations due to the change of wind speed and grid conditions may cause flicker emission. Moreover, the main problem of the fixed speed wind turbine is flicker. Therefore, the assessment of power quality in such systems, especially in term of flicker emission, is a very important issue. This thesis presents the effects of wind turbine installation on flicker emission during continuous operation, namely wind characteristics and grid conditions. The effects of penetration levels and types of wind turbine are investigated in this study. A flickermeter based on IEC 61000 - 4 - 15 is used to evaluate the flicker severity. Installing a series capacitor can help mitigating the emission of voltage flicker. The distribution system used in this study is limited to one practical test system in Samoeng District, Thailand. The simulation and modeling have been implemented by using DIgSILENT PowerFactory software.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Energy
Thesis (M.Eng.) - Asian Institute of Technology, 2014
Keywords: Wind turbines -- Evaluation; Wind turbines -- Control